LEARNING TASKS’ WHAT AND HOW: PERSPEKTIF DOSEN DAN MAHASISWA MENGENAI TUGAS PEMBELAJARAN - Gusrayani, Diah (Mimbar Sekolah Dasar, 2015)
The ability to design authentic and meaningful learning task is one of thousands preconditions of teachers. Findings shown that elementary school teachers could not be able to design and apply meaningful tasks in and after the teaching time (Rohayati, 2007; Hamzah, 2009; Budimansyah; 2009). PGSD UPI as one of the institutions preparing elementary teachers to be should concern more on this condition. The curriculum designed here should reflect the needs of elementary school teachers to be especially their needs of realizing the goals and objectives that have been established previously by the institution, and how they are reflected through learning tasks in the classroom, especially the classroom for these teachers to be in PGSD Kampus Sumedang. Therefore, the research selects participants from that site, 126 students and 28 lecturers. They were given questionnaires designed in line with three research questions: 1) how do students and lecturers perceive learning tasks? 2) how are students’ and teachers’ roles in collecting the data for learning tasks? 3) has the learning tasks thus far been designed to meet the standardized of authentic tasks? 4) how lecturers and students perceive feedback for their learning tasks? The result shows that the perception of students and lecturers toward learning tasks influence how they behave toward it, hence, if once it has been found misperceived, the construction is need of revisiting.Keywords: learning task, feedback, authentic task, goals, objectives.